Work Life Balance pada Generasi Z Pekerja Gig Economy - Arum Pandan Sari (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
The rise of the digital era has significantly accelerated the growth of the gig economy, which is particularly attractive to Generation Z (Gen Z) due to its flexibility and autonomy. However, this work model also presents unique challenges in maintaining a healthy work-life balance. This study aims to examine the level of work-life balance among Gen Z workers in the gig economy and to identify the influencing factors. A quantitative approach was employed by distributing questionnaires to 150 Gen Z gig workers aged 18–27, engaged in sectors such as ride-hailing, digital freelancing, and food delivery services. The results indicate that most respondents experience an imbalance between work and personal life, primarily due to irregular work hours and income instability. Social support and control over working time were found to have a positive influence on achieving work-life balance. These findings highlight the need for more adaptive labor policies to accommodate the well-being of young workers in informal and flexible work environments.